2008
DOI: 10.1016/j.juro.2008.04.020
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Nephrostomy Placement Versus Tubeless Percutaneous Nephrolithotomy

Abstract: This trial demonstrates that percutaneous nephrolithotomy without nephrostomy or stent is a safe and well tolerated procedure in selected patients. Length of stay was reduced with no major complications in either group. We believe that totally tubeless percutaneous nephrolithotomy may be considered an accepted standard of care for selected cases and it is possible to reserve placement of a nephrostomy tube or internal ureteral stent for specific indications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 17 publications
3
71
0
1
Order By: Relevance
“…The present novelty in PCNL is "tubeless" which has shown reduced complication rates. [5][6][7][8] But many other studies in the literature have shown that placement of a nephrostomy tube is mandatory. [1,3] Karakose et al [9] have done a study comparing smaller Amplatz sheath versus larger Amplatz sheath and have shown that complications are less with Amplatz sheaths of smaller size.…”
Section: Discussionmentioning
confidence: 99%
“…The present novelty in PCNL is "tubeless" which has shown reduced complication rates. [5][6][7][8] But many other studies in the literature have shown that placement of a nephrostomy tube is mandatory. [1,3] Karakose et al [9] have done a study comparing smaller Amplatz sheath versus larger Amplatz sheath and have shown that complications are less with Amplatz sheaths of smaller size.…”
Section: Discussionmentioning
confidence: 99%
“…15 There have been significant advances in the percutaneous extraction of renal calculi. [2][3][4][5][6][7][8][9][10] Review articles have highlighted the need for minimal intra-operative bleeding, negligible residual stone burden, and one to two attempts at renal access when considering tubeless approaches. Recently, the ability to perform tubeless PCNL as an outpatient procedure has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] Tubeless PCNL, with ureteral stenting, has been shown to decrease patients' analgesic requirements and hospital length of stay. 9,10 Although hospitalization is standard practice after PCNL, reports have described success with outpatient management. 11,12 This case report is the first to describe successful outpatient PCNL in a renal transplant patient.…”
Section: Introductionmentioning
confidence: 99%
“…3 Numerous studies have supported the use of the tubeless method as a viable alternative to standard PCNL. 1,[4][5][6][7] The advantages of tubeless PCNL over the standard procedure include reduced postoperative analgesic requirements, as well as reduced duration of hospitalization without an increase the rate of complications. Surgical advancements have enabled the use of tubeless PCNL in complex cases, including pediatric, geriatric and bilateral simultaneous renal calculi.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies to date have demonstrated that this is a safe and effective method of stone burden clearance in select patients. 1,[3][4][5][6][7] Recently, tubeless PCNL, on an outpatient basis, has been reported. 8,9 This case report is the first to describe a case of outpatient bilateral tubeless PCNL in a patient with bilateral large staghorn calculi.…”
Section: Introductionmentioning
confidence: 99%